Aeration performance of triangular notch weirs at recirculating system - Baylar, A; Bagatur, T; Tuna, A (Iwa Publishing, 2001)
An adequate supply of dissolved oxygen is essential for the survival of aquatic organisms. Hydraulic structures can increase dissolved oxygen levels by creating turbulent conditions, where small air bubbles are carried into the bulk of the flow. Plunging overfall jets from weirs at recirculating systems are a particular instance of this. This paper seeks triangular notch weirs having different weir angle (alpha) and how they affect the aeration performance. It is demonstrated that the aeration efficiency of a 90 degrees triangular notch weir is generally better than that of the other weirs.
Keywords: oxygen transfer; oxygen transfer efficiency; dissolved oxygen; aeration; triangular notch weirs